SOSIALISASI STRATEGI USAHA KECIL MENENGAH UNTUK MENINGKATKAN PRODUKTIVITAS PASCA PANDEMI VIRUS COVID19 - Sudiman Sudiman; Wakit Ahmad Fahrudin; Taufik Taufik; Karya Subarman; Agus Taufik (Abdi Laksana : Jurnal Pengabdian Kepada Masyarakat, 2020)
Micro, Small and Medium Enterprises (MSMEs) have an important and strategic role in national economic development. Besides playing a role in economic growth, it also plays a role in employment. Based on data from the Ministry of Cooperatives and Small and Medium Enterprises in 2018 the number of MSMEs in Indonesia is 64,194,057, while the absorption of MSME workers is 116,978,631. The number of MSMEs in South Tangerang City according to the Office of Cooperatives and Small and Medium Enterprises in South Tangerang City is 26,700. Covid-19 began to hit Indonesia in February 2020. Covid-19 was not just a health disaster, it also caused chaos in the economic sector, not only large industries that were exposed, it also included MSMEs in Indonesia. Efforts should be made to help MSMEs to recover and increase their business activities so that productivity and turnover will gradually increase again. To that end, the Community Service Team (PKM) of the Industrial Engineering Study Program of the University of Pamulang (UNPAM) consisting of Lecturers and Students helps MSMEs principals especially in Serpong Village, Setu District, South Tangerang City. In carrying out its business, SMEs are expected to implement seven tips for success in business and must be able to see opportunities and challenges going forward besides the need to understand the tin main problem in the business.Keywords: MSME, Covid-19, ProductivityKeywords:UMKM, covid-19, produktivity